Militares, Mocambos e o viver ao modo indígena na fronteira entre Pará e Maranhão (1790-1830) - Sueny Diana Oliveira de Souza (Caravelle)
This papers deals with the “control” that Parà and Maranhão’s authorities tried to exert upon Indigenous populations in accordance with the Central Government’s rules concerning the border between the two harbor offices which was set on the Turiaçu river, as well as a larger control of populations in Turiaçu’s region between 1790 and 1830. In this vast border territory, runaway slaves, soldiers, deserters and natives knew the local geography and took advantage of the refuges provided by forests and rivers. Therefore, many of these individuals turned this region into their den where they settled in large and complex Maroon comunities.